Religion without Belief and Community in Africa - Kroesbergen, Hermen (Religions, 2019)
Religion in Africa is in many respects becoming religion without belief and community again, I will argue in this article. Europeans arriving in Africa did not recognize African religion, because Africans did not have the kind of belief and community characteristic of European concepts of religion. Pentecostalization brings back this African concept of religion without worship groups defined by an adherence to a particular picture of the world, and I will show what this means at grassroots level. What matters in this concept of religion is whether something works rather than some implied truth-claims about the world. Instead of forming groups, Neo-Pentecostal ministries are more often organized around the vertical relationship between the man/woman of God and his/her client. The Pentecostalization of Christianity in Africa has led to a form of religion in which beliefs and community are not of central importance.